DEVELOPMENT OF NEW APPROACHES TO MODELING DIAGNOSTIC PROCESSES AND RISK ANALYSIS IN IT COMPANIES - IVCHENKO, Iryna; FILATOVA, Tetiana; IVCHENKO, Oleн (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article considers the topical issue of developing new approaches to modeling the processes of diagnostics and risk analysis in IT companies. The rapid technological progress of recent years necessitates innovative risk management methods. The authors highlight that conventional risk assessment methods often fail to account for the swift changes within the IT sector and may prove inadequate for dynamic environments. Consequently, the task at hand involves formulating and adapting new risk modeling approaches that consider the specific nature of the IT industry and propose enhancements to risk management. The article underscores that one of the primary sources of risk for IT companies is the rapid technological progress within the IT realm. Novel technologies frequently employed by IT companies can be less predictable and stable compared to those utilized by traditional businesses. Conventional risk models, founded on historical statistical data, may be ill-suited for such dynamic environments, necessitating fresh approaches to modeling technological and innovative risks.Within the article, three key risk sources within the IT domain are examined: rapid technological progress, cybersecurity threats, and the need to handle extensive data volumes. The main risks associated with these factors are described, highlighting the need for developing new approaches to their modeling. Emphasis is placed on cybersecurity and cyberattacks, which present significant threats to IT companies. Thus, particular attention is dedicated to the economic-mathematical modeling of cyber risks, avenues of research in this field, and effective risk management. The authors underscore the importance of leveraging cutting-edge technologies, notably artificial intelligence, in modeling risks for IT companies. The article demonstrates how the utilization of new risk modeling methods can assist in identifying potential threats and devising effective measures for prevention. As a result of this research, it is affirmed that the development of innovative risk modeling approaches in IT companies holds substantial potential for ensuring business resilience.
Keywords: risk modeling; information technologies; IT company; cyber risks; technological development of the IT sphere; digitalization